Desempenho operacional de colhedora de forragem com diferentes tamanhos de partículas com e sem o uso do processador - Paludo, Vinícius [UNESP] (2015)
This study aimed to assess the energy consumption of the forage harvester used in the mechanized operation of whole corn plant forage crop, with reference to the processing of this material in different particle sizes. The test was conducted at the Experimental Farm Lageado, belonging to the Faculty of Agricultural Sciences - UNESP, located in Botucatu - SP, in the center west region of São Paulo. The selected treatment were related to six different settings mass particle size of the crop, where the particle size was started in 5 millimeters (mm) reaching 30 mm (increasing the particle size 5mm to each treatment) and varying the use of CrossOver Rotor system on and off. In the experiment, the experiment was on track for a better utilization of the available area, where within each group were analyzed 7 reps. Each of 12 experimental groups was 105 m long and 6 m wide, totaling area of 7560 m². Statistical analyzes were performed using the SUM program, the average Tukey test at 5% probability. The results showed that from average 4 sizes of corn particles processed energy consumption of the machine suffered little or no statistical difference. Automotive and recommended harvester for silage process. The rotor use proved to be beneficial to the producer without cost increases. Treatment with attached rotor and smaller particle size always differed from other treatments, with higher fuel consumption values than the other treatments.